The riddle of all constitutions - Marks, Susan (Oxford University Press, 2000)
The book examines current debates about the emergence of an international legal norm of democratic governance and also considers some of the wider theoretical issues to which those debates give rise. It asks should international law seek to promote democratic political arrangements? If so, on what basis, and using which of the many competing conceptions of democracy?